Enhanced calcium responses to serotonin receptor stimulation in T-lymphocytes from schizophrenic patients – A pilot study. (4th March 2015) - Genius, J.; Schellenberg, A.; Tchana-Duope, L.; Hartmann, N.; Giegling, I.; Hartmann, A.; Benninghoff, J.; Rujescu, D.
Highlights: Peripheral cells (T-lymphocytes) permit the non-invasive investigation of receptor-mediated signaling in the brain. The serotonin system may be implicated in the pathogenesis of schizophrenia. Intracellular calcium peaks after serotonin stimulation are abnormally high in clinically stable schizophrenic patients. Unspecific stimulation with the mitogenic PHA does not elicit abnormal responses. Abstract: Even if more extensively investigated in affective disorders, the serotonergic system is likely to be also implicated in modulating the pathogenesis of schizophrenia, where it closely interacts with the dopaminergic and glutamatergic system. To substantiate this notion, we studied the intensity and dynamics of cellular Ca 2+ responses to serotonin (5-hydoxytryptamine, 5-HT) in peripheral lymphocytes taken from currently non-psychotic schizophrenic patients. To this aim, peripheral lymphocytes were freshly obtained from healthy controls and a naturalistic collective of patients with schizophrenia in remission. Intracellular Ca 2+ responses were recorded in real-time by ratiometric fluorometry after 5-HT or phythaemagglutinin (PHA) stimulation, which served as an internal reference for Ca 2+ responsivity to non-specific stimulation. The intracellular Ca 2+ peak early after applying the 5-HT trigger was significantly elevated in schizophrenic patients. No significant differences of Ca 2+ peak levels were seen in response to stimulation with the mitogenic agent PHA, although responses to 5-HT and PHA were positively correlated in individual patients or controls. In conclusion, the serotonergic response patterns in peripheral lymphocytes from schizophrenic patients seem to be elevated, if employing sensitive tools like determination of intracellular Ca 2+ responses. Our observations suggest that the participation of serotonergic neurotransmitter system in the pathogenesis of schizophrenia may deserve more interest, even if it should only act as a modulator on the main pathology in the dopaminergic and glutamatergic systems. We hope that this pilot study will prompt further studies with larger patient collectives to revisit this question.